The Effect of Peppermint Aromatherapy (Mentha Piperita Leaf) On Reducing Post Dural Puncture Headache Pain in Post-Spinal Anesthesia Patients - Riski Ardi Saputro; Suandika, Made; Sukmaningtyas, Wilis (Global Indonesia Health Care (GOICARE), 2025)
Background: Post-Dural Puncture Headache (PDPH), as observed clinically, is one of the most common complications of spinal anesthesia. It generally develops within 12-72 hours of the procedure. Though there are pharmacological treatments, these have largely been overshadowed by several tried-and-tested non-pharmacological techniques, which include peppermint aromatherapy, in relieving symptoms of PDPH. Purpose: This study was aimed at determining the effectiveness of peppermint aromatherapy in reducing head pain associated with PDPH among post-spinal anesthesia patients at Cilacap Regional General Hospital. Methods: A quasi-experimental study design with one group and pretest-posttest design was conducted on 39 patients experiencing PDPH. Pain was measured using the Numeric Rating Scale (NRS) prior to and post-administration of peppermint aromatherapy. The intervention was two drops of peppermint aromatherapy mixed with 100 ml of mineral water and inhaled through the humidifier for 15 minutes. Wilcoxon tests were done for statistical analysis. Results: The mean PDPH pain level before the intervention was 5.69. After inhaling peppermint aromatherapy, the mean pain level dropped significantly to 1.64 (p < 0.05). The results are interpreted with respect to the significance indicated by this difference in levels while comparing PDPH symptoms before and after treatment with peppermint aromatherapy. Conclusion: Hence, peppermint aromatherapy is a highly effective treatment modality for both patients suffering from PDPH and those who have undergone spinal anesthesia. It could be recommended as a non-pharmacological adjunct therapy in the management of PDPH. Further validations of the findings are needed through a larger sample size and controlled groups.